1995
DOI: 10.1002/jor.1100130514
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent changes in the response of cartilage to static compression suggest interstitial pH is not the only signaling mechanism

Abstract: The goal of the present study was to reexamine the role of interstitial pH in regulating the biosynthetic rate in cartilage tissue by addressing two research questions: (a) Do small, short-term changes in interstitial pH, induced independently by two different mechanisms (namely, by controlling the pH of the medium or by mechanical compression), result in biosynthetic rates commensurate with those expected from the "natural" relationship between interstitial pH and biosynthesis? and (b) Are the effects of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Tissues subjected to static compressive forces were also more hydrated, which probably reflected the smaller amount of collagen accumulated in these cultures [33, 361. These observations are in keeping with other studies that have demonstrated the detrimental effects of static compressive forces on the quality of the cartilage extracellular matrix [3,16,33,37].…”
Section: Discussionsupporting
confidence: 92%
“…Tissues subjected to static compressive forces were also more hydrated, which probably reflected the smaller amount of collagen accumulated in these cultures [33, 361. These observations are in keeping with other studies that have demonstrated the detrimental effects of static compressive forces on the quality of the cartilage extracellular matrix [3,16,33,37].…”
Section: Discussionsupporting
confidence: 92%
“…Confinement either results in increased collagen organization as seen in the radial confinement experiment, or increased matrix synthesis as seen in the passive axial compression experiment. Although using immature bovine cartilage explants, Boustany et al 35 also found that static compression of <25% strain for 60 h increased the biosynthetic rate of GAG and collagen production, although the mechanical properties were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…31 Following preconditioning, specimens were exposed to incremental stress relaxation, whereby they were exposed to 15 min constant strain increments until failure. A maximum of 11 increments were allowed (4,8,12,16,20,25,35,50,70, 100, and 130% strain). A strain rate of 6 mm/min was employed between constant-strain increments.…”
Section: Tensile Testingmentioning
confidence: 99%
“…The relatively simple case of a ramp-and-hold static compression of cartilage can result in transient interstitial fluid expression, cell deformation (25), increased osmolarity (26), decreased extracellular pH (27), changes in fixed charge density (28), and altered transport of soluble factors within the tissue (22). Each of these physical phenomena may potentially act as a "mechano-ligand" activating or inhibiting one or more signaling pathways.…”
mentioning
confidence: 99%